Allergic Rhinitis among the Inhabitants of Santasi-Apire in the Ashanti Region, Ghana - Opoku Agyemang, Cecilia; Oscar Agyemang Opoku (The Indonesian Institute of Science and Technology Research, 2025)
Allergic rhinitis often co-occurs with common illnesses, such as rhinosinusitis, asthma, and otitis media with effusion, which significantly contributes to the severity of these conditions and negatively impacts the individuals’ quality of life. Additionally, the pathogenesis of most upper and lower respiratory illnesses is affected by the presence of allergic rhinitis, according to the World Allergy Organization (WAO). The study aimed to assess the knowledge, prevention, and management of Allergic Rhinitis among inhabitants of Santasi-Apire in the Ashanti Region, Ghana. The study was a descriptive cross-sectional study with a quantitative technique. The target population was inhabitants aged 15 years and above. A sample size of 100 was selected for the study using a stratified sampling method. Ethical clearance was sought from Kumasi Metropolitan and the health directorate Committee for data collection using both open and closed types of questionnaires which were structured according to the objectives of the study. Data collected were collated, compiled, and analyzed using Statistical Package for Social Science Software (SPSS) version 20.0 and results were presented in the form of tables and charts according to their frequencies and percentages. The study discloses that most Allergic Rhinitis cases are triggered by dust, of which rhinorrhea the most is evidenced as the sign and symptom. Inhabitants of the Santasi-Apire community know that allergic rhinitis is a life-threatening condition. However, sprinkling water, avoidance of dusty areas, smoking, and triggers of allergic rhinitis are the preventive measures used by Santasi-Apire inhabitants.